Asians in the West - Hoyt, Edwin Palmer (Nashville : T. Nelson, 1974)
Traces the history of Asian immigration to the United States and discusses the experiences and problems of various oriental groups trying to settle and assimilate into American society.
Includes index.
Bibliography: 151-152.
Keywords: Asian Americans -- History